Eficiencia de procedimientos registrales y calidad de servicio en Superintendencia Nacional de Registros Públicos - Oficina Descentralizada Registral de Sánchez Carrión - 2017 - Ramos Rondón, Amelia Valvina (2018)
The present investigation has been carried out in the Province of Sánchez Carrión - La Libertad Region, being the object of study the National Superintendency of Public Registries. Its general objective was to determine how the Efficiency of the Registry Procedures is related to the Quality of Service to the User in the National Superintendence of Public Registries - Decentralized Office of Sánchez Carrión Registry, Year 2017. This being the case, the design of the investigation was not experimental cross section; its population consisted of 5 workers and 300 users of the National Superintendency of Public Registries, being the respectful sample of 5 workers and 55 users. For data collection, the survey technique was applied, with the instrument being the questionnaire. According to the results obtained and analyzed, the hypothesis that establishes the Efficiency of the Registry Procedures is positively related to the Quality of Service to the User in the National Superintendence of Public Registries - Decentralized Registry Office of Sánchez Carrión, Year 2017. As well as the main conclusion that the Efficiency of the registry procedures is related in a "positive moderate" way to the Quality of Service to the User in the National Superintendence of Public Registries - Register Office of Sánchez Carrión, as determined by the Pearson correlation coefficient (r = 0.716); this indicates that if the independent variable improves (efficiency) it also improves moderately the dependent variable (quality of service). Administrative procedures, as well as the quality of service to the user, the use of surveys and the implementation of suggestions; this means that weaknesses that require corrective action.